Peningkatan Gerak Dasar lokomotor dan manipulatif melalui Metode Permainan dalam pembelajaran jasmani pada siswa Kelas V SDN Sukakarya 2 Kota Sukabumi - Alfiansyah, Andys Muhammad Gilang; Maulana, Firman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this research was carried out to determine the improvement of learning methods for locomotor movement and manipulative material, using game methods for class V students at SDN Sukakarya 2 Sukabumi City. This research uses the classroom action research (PTK) method with the Kemmis and Mc taggers models, data management uses Microsoft Excel. implemented in two cycles for class V students at SDN Sukakarya 2 Sukabumi City with a total of 24 students from April 30 2024 to May 20 2024. The results of the scores in the first cycle from 24 class V students of SDN Sukakarya 2 Sukabumi City got an average running technique score of 1.29, an average throwing technique score of 1.08, an average jumping score of 1.69, an average technical score of kicked 1.25, the result of all students was 4.79. The results of the second cycle mean running technique 2.87, throwing technique 2.91, jumping technique 2.75, and kicking technique 3.2. The sum of the scores for all aspects from 24 students is 11.7. The research results show that game-method learning can improve. Conclusion, regarding the learning of class V students at SDN Sukakarya 2 Sukabumi City in learning the techniques of running and throwing, jumping, and kicking. Using the game method can improve students' psychomotor skills. Keywords: Basic Movements, Game Methods, Learning Results